Restorative Justice Approach for Children Who Commit Crimes During Demonstrations: Law Enforcement and Future Arrangements - Ni Nyoman Ayu Risna Maryuni; A.A.A Ngr. Tini Rusmini Gorda; I Gede Agus Kurniawan (Faculty of Law, Universitas Pekalongan, 2025)
Demonstrations are one form of community effort to channel their rights and express their opinions. Basically, demonstrations have been regulated in various laws and regulations, particularly to ensure that those demonstrating are adults and can do so in a conducive and law-abiding manner. In practice, there are children, particularly school-aged children, who participate in demonstrations without knowing their purpose or goals, and instead engage in actions that damage facilities and break the law. This research aims to analyze the Restorative Justice approach for children, particularly when children face the law, such as when they participate in demonstrations. This research is normative legal research with a conceptual and legislative approach. The research findings confirm that, based on various laws and regulations, children are not permitted to participate in demonstrations, but the state is still obligated to provide space and facilitate children in expressing their aspirations and rights. Regarding children who commit unlawful acts while participating in demonstrations, law enforcement agencies, particularly the police, must optimize the Restorative Justice approach by involving parents, teachers/educators/community leaders, and the Indonesian Child Protection Commission (KPAI) to ensure that children who commit unlawful acts during demonstrations can understand their mistakes without losing their rights to grow and develop. This research recommends legal updates to regulations governing public expression, emphasizing a Restorative Justice approach for children who commit legal violations during demonstrations